Prevalence of Schistosoma infection and associated factors among pregnant women attending antenatal care at Shewa Robit Health Center, North-Central Ethiopia: a cross-sectional study - Woubshet Zewdie; Getaneh Alemu; Tadesse Hailu (Tropical Medicine and Health)
Abstract Background Schistosoma spp. and other intestinal parasites are common in Ethiopia. During pregnancy, SCH increases the risk of adverse birth outcomes. However, its epidemiology among pregnant women and awareness level about the disease are not well addressed in Ethiopia. This study was conducted to address this gap. Methods A cross-sectional study was conducted from April to June 2023 among 422 pregnant women who attended Shewa Robit Health Center. Pregnant women who came to the health center for antenatal care services were enrolled in the study following systematic random sampling technique. Questionnaire data was collected on socio-demographic characteristics, KAP towards SCH, and associated factors. Stool samples were processed using the Kato–Katz technique, while urine samples were tested with urine test strips for hematuria, and filtration and centrifugation methods for detection of S. haematobium. Data were entered and analyzed using SPSS software version 25. Descriptive statistics and logistic regression were performed at a 95% confidence level. Results Among 422 pregnant women, 38 (9.0%) were positive for hematuria, but none were infected by S. haematobium. Schistosoma mansoni was detected in 40 (9.5%; 95% confidence interval (CI): 6.6–12.6) participants. Habit of swimming or bathing (adjusted odds ratio (AOR) = 4.896; 95% CI: 2.193–10.933, p < 0.001) and habit of crossing freshwater on barefoot (AOR = 5.113; 95% CI: 1.171–22.324, p = 0.030) were significantly associated with S. mansoni infection. Of the participants, only 74 (17.5%) had previously heard of SCH. Out of 74 aware participants, 49 (66.2%) and 14 (18.9%) were unaware of the causative agent and possibility of a cure for SCH, respectively. Sixty-one (82.4%) were aware that SCH is preventable. Fifty-three (71.6%) and 4 (5.4%) participants believed that SCH is preventable and serious disease, respectively. Eight (10.8%) and 9 (12.2%) participants avoided contact with freshwater and used clean water for drinking and washing, respectively. Conclusions There is nearly moderate prevalence of S. mansoni infection in the study area. Pregnant women who often had freshwater contact were more likely to contract S. mansoni. Most pregnant women in the study area had low KAP levels towards SCH. Therefore, women of reproductive age groups should be the focus of SCH control programs.